Methods of corporate information system management on the basis of optimal control theory - Савченко, Аліна Станіславівна (Science-based technologies, 2020)
To manage corporate information systems that include a large number of active equipment, you need complex systems that monitor, control and manage each element and state of the system as a whole. Finding the optimal delineation of both the functions of the central part of the SU and the management functions of the autonomous segment, and the actual division into autonomous segments is important because it directly affects the efficiency of management. The question of the optimal management of the information system as a whole is still unresolved. Therefore, the development of a method of information system management using the theory of optimal control is appropriate and relevant. For corporate information systems, optimal management should provide a minimum criterion of optimality under given constraints. That is, the minimum cost of control (control signals in the form of protocols). It should also be borne in mind that not every optimal solution, synthesized theoretically, can be implemented in practice on the basis of the existing prior art. The theory of automatic optimal control in its traditional forms cannot be the only basis of the network management system. It should be integrated with other promising areas, such as artificial intelligence systems and a methodology for describing complex under-formalized systems. The method of corporate information system management based on the theory of optimal management assumes that the first stage in the sequence of receiving, storing and processing information in the system is the stage of determining (recognizing) the state using image recognition methods. The next stages of the proposed method are the formation of a strategy for optimal management, development and implementation of management actions based on it using existing protocols. On the basis of the developed method the general structural scheme of SU by the information system consisting of several autonomous segments is offered and protocols for its realization are resulted and defined.